Empowering School Quality: The Impact of Principal’s Managerial Skills and School Culture in Public Elementary Schools - Ambar Sekti; Soedjono Soedjono; Aryo Andri Nugroho (AL-ISHLAH: Jurnal Pendidikan, 2025)
Improving school quality remains a critical challenge in elementary education, particularly in rural and semi-urban contexts where leadership capacity and organizational conditions vary considerably. Previous studies have highlighted the importance of principals’ managerial skills and school culture; however, limited research has examined their combined influence on school quality within an integrated theoretical framework. This study employed a quantitative ex-post facto design to examine the relationships among principals’ managerial skills, school culture, and school quality in public elementary schools in Boja District, Kendal Regency. Data were collected from 103 teachers selected through proportional random sampling using a structured Likert-scale questionnaire. Descriptive statistics, simple linear regression, and multiple regression analyses were conducted to assess both individual and combined effects of the independent variables on school quality. The findings indicate that principals’ managerial skills have a significant positive relationship with school quality (R² = 0.535), as does school culture (R² = 0.526). When examined simultaneously, principals’ managerial skills and school culture jointly explain 70.3% of the variance in school quality, indicating a strong and complementary association between leadership capacity and organizational culture. These results suggest that principals’ managerial skills contribute to school quality not only directly but also through the development of a positive school culture that supports effective teaching and learning. The study underscores the importance of integrated leadership and cultural development strategies in improving school quality, particularly in resource-limited educational contexts.